PENGARUH METODE SMALL GROUP DISCUSSION TERHADAP KEPATUHAN DIET PASIEN DIABETES MELITUS TIPE 2 DI DESA BENER KELIPAH UTARA KECAMATAN BENER KELIPAH KABUPATEN BENER MERIAH TAHUN 2021 - Kamaliah Ainun; Kristina; Niasty Lasmy Zaen (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Diabetes mellitus is a metabolic disease with hyperglycemia characteristics. High non-compliance is in the amount of food consumed by respondents, which is 84.4%. One of the DM management to prevent complications of DM patients is diet therapy or dietary management. The purpose of this study was to determine the effect of the Small Group Discussion Method on Diet Compliance in Type 2 DM patients.This type of research uses a quantitative approach with a one group pre post test design. The sample of this study was 25 respondents who were selected through a total sampling technique. The location of this research is in Bener Kelipah Utara Village, Bener Kelipah District, Bener Meriah Regency. The instrument used was a 3J diet adherence questionnaire on schedule, type, amount. And using the Wilcoxon test. The results of this study showed that dietary compliance before being given health education, 5 (20.0% of respondents were quite obedient. After health counseling, showed higher dietary compliance 16 (64.0%) of respondents were quite obedient in diet. By using the Wicoxon test, and the result is that Ha is accepted with a value of 0.01. Conclusions, namely: before being quite obedient 5 (20.0%), respondents. While after quite obedient as many as 16 (64.0%) respondents. And the influence of the small group discussion method on the adherence to the diabetes mellitus diet, that is, after the pre-test and post-test, Ha received a value of sig.2 (tailed) 0.01. Suggestions for research sites to consider providing education/information as an alternative in learning about the level of dietary compliance, it is hoped that future researchers can conduct further research on the effect of the small group discussion method on dietary compliance in type 2 diabetes mellitus patients.